Tumor response after long interval comparing 5x5Gy radiation therapy with chemoradiation therapy in rectal cancer patients. Issue 7 (July 2018) - Rombouts, A.J.M.; Hugen, N.; Verhoeven, R.H.A.; Elferink, M.A.G.; Poortmans, P.M.P.; Nagtegaal, I.D.; de Wilt, J.H.W.
Abstract: Background: In the era of organ preserving strategies in rectal cancer, insight into the efficacy of preoperative therapies is crucial. The goal of the current study was to evaluate and compare tumor response in rectal cancer patients according to their type of preoperative therapy. Methods: All rectal cancer patients diagnosed between 2005 and 2014, receiving radiation therapy (RT, 5 × 5Gy; N = 764) or chemoradiation therapy (CRT; N = 5070) followed by total mesorectal excision after an interval of 5–15 weeks were retrieved from the nationwide Netherlands Cancer registry. Logistic regression was used for multivariable analysis. Results: Median age of patients treated with RT was 76 years (range 28–92) compared to 64 years (range 21–92) for patients treated with CRT (P < 0.001). Patients treated with RT had a significantly lower clinical stage (P < 0.001). A complete pathologic response (ypT0N0) was found in 9.3% of patients treated with RT, significantly less than in patients treated with CRT (17.5%; odds ratio [OR] 0.37, 95% confidence interval [CI] 0.24–0.57). A good response (ypT0-1N0) was observed in 17.5% of patients treated with RT and in 22.6% of patients treated with CRT (OR 0.70, 95% CI 0.51–0.95). Histological subtype, clinical stage and distance to anus were identified as independent predictors for tumor response. Conclusions: Despite a more advanced clinical stage, complete pathologic response was more common in patients treated with CRT than in patients treated with RT. Prospective trials are needed to establish the differences in other outcome parameters, including the impact on organ preserving strategies.